Determination of groundwater-pit lake interactions, Liberty Pit, Tonopah, Nevada, USA - Bowell, RJ; Anderson, B; Kruger, R; Clarkson, B; Chutas, N; Carpenter, A; Parshley, J (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
This paper presents a case study of an open pit acting as a terminal sink in a net evaporative environment. The Liberty Pit, located on the Tonopah project in Nye County, Nevada, hosts a small permanent body of water. Currently, this body was approximately 12 m deep with a diameter of approximately 20 m in a crude circular shape. The geology of the pit is dominated by a Quartz Monzonite Porphyry (QMP) that hosts copper-molybdenum mineralization in a porphyry style deposit. Additional mineralization is also hosted within fingers of a mineralized host rock, potassic altered hornfels, that also outcrop in the pit. The most striking geological feature in the pit is the Liberty fault, which is a listric fault, that occupies the western portion of the pit and separates overlying Neogene-Quaternary alluvium from the underlying Mesozoic bedrock. In terms of hydrogeological setting, water in the pit area is separated from the regional groundwater, which is compartmentalized by bedrock faults. Water chemistry of the monitoring boreholes on the perimeter of the pit show distinct chemistry including isotopic signature compared to an in-pit shallow borehole and the pit lake. Trace element and isotopic signature of the groundwater indicates it may be a source for the pit lake water demonstrating the pit is acting as a hydrologic sink. This is further confirmed by hydrogeological calculations that demonstrate the pit lake is isolated from the main bedrock groundwater through the presence of an aquiclude, the Liberty fault. Geochemical modelling of the pit lake, coupled with hydrogeological estimates of inflows, demonstrate how the pit lake chemistry can be described in terms of inflow groundwater coupled with meteoric flushing of secondary salts and evapoconcentration. The lake body appears to currently be homogeneous with little evidence of zonation. This study demonstrates the merits of field data and actual monitoring data in the evaluation of a pit lake. Despite the location on the side of basin and range topography, the lake is isolated from regional groundwater through the presence of natural aquicludes and, thus, does not present a risk to regional groundwater.
Keywords: Pit Lake; Stable Isotopes; Hydrogeology; Groundwater Interaction